2013
DOI: 10.1073/pnas.1311887110
|View full text |Cite
|
Sign up to set email alerts
|

Brief meditation training induces smoking reduction

Abstract: More than 5 million deaths a year are attributable to tobacco smoking, but attempts to help people either quit or reduce their smoking often fail, perhaps in part because the intention to quit activates brain networks related to craving. We recruited participants interested in general stress reduction and randomly assigned them to meditation training or a relaxation training control. Among smokers, 2 wk of meditation training (5 h in total) produced a significant reduction in smoking of 60%; no reduction was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
119
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 56 publications
9
119
0
2
Order By: Relevance
“…Importantly, the present study shows preliminary results corroborating the idea that some meditation benefits may take effect since an early stage of practice (Tang et al, 2007;Tang et al, 2013;Taylor et al, 2011;Zeidan et al, 2010aZeidan et al, , 2010b). Nevertheless, it should be noted that comparing novice and expert practitioners yields distinct effects.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Importantly, the present study shows preliminary results corroborating the idea that some meditation benefits may take effect since an early stage of practice (Tang et al, 2007;Tang et al, 2013;Taylor et al, 2011;Zeidan et al, 2010aZeidan et al, , 2010b). Nevertheless, it should be noted that comparing novice and expert practitioners yields distinct effects.…”
Section: Discussionsupporting
confidence: 86%
“…Another example of implication relates to the finding that a brief meditation training was able to reduce cigarette craving (Tang et al, 2013). We suggest this reduction might have resulted from the meditators' ability to better control the interference of cues associated with the drug, and to reduce attentional bias to these stimuli, which are processes known to normally lead to craving or to the drug use behavior (Peuker, Lopes, Menezes, Cunha, & Bizarro, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…More than 80 % of addicted individuals fail to seek treatment, which might reflect impairments in recognition of severity of disorder [28,29]. There is preliminary evidence that mindfulness meditation can reduce substance use, perhaps through one or more of these hypothesized pathways [51,52]. For example, one study of mindfulness-naive smokers demonstrated reduced connectivity between craving-related brain regions during a mindfulness condition compared to passive viewing of smoking-related images during cigarette craving [53], suggesting a functional decoupling of involved regions.…”
Section: Clinical Studies and Implications Of The Translational Prevementioning
confidence: 99%